2020
DOI: 10.3389/fonc.2020.01629
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trials for Artificial Intelligence in Cancer Diagnosis: A Cross-Sectional Study of Registered Trials in ClinicalTrials.gov

Abstract: Objective: Clinical trials are the most effective way to judge the merits of diagnosis and treatment strategies. The in-depth mining of clinical trial data enables us to grasp the application trend of artificial intelligence (AI) for cancer diagnosis. The aim of this study was to analyze the characteristics of registered trials on AI for cancer diagnosis. Methods: Clinical trials on AI for cancer diagnosis registered on the ClinicalTrials.gov database were searched and downloaded. Statistical analysis was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…For status, 23 (37.70%) were Characteristics of Trials at ICU Table 5 shows the characteristics of trials on AI conducted in emergency department. Among the 85 trials, 48 (56.47%) were interventional trials, and 37 (43.53%) were observational A total of 146 registered trials were identified, including 61 trials in ED and 85 in ICU, which is similar with our previous study for cancer (33). Over half trials registered after 2017, and it was consistent with the development of industry 4.0, which depended on AI to empower medicine (37).…”
Section: Observational Studysupporting
confidence: 72%
See 2 more Smart Citations
“…For status, 23 (37.70%) were Characteristics of Trials at ICU Table 5 shows the characteristics of trials on AI conducted in emergency department. Among the 85 trials, 48 (56.47%) were interventional trials, and 37 (43.53%) were observational A total of 146 registered trials were identified, including 61 trials in ED and 85 in ICU, which is similar with our previous study for cancer (33). Over half trials registered after 2017, and it was consistent with the development of industry 4.0, which depended on AI to empower medicine (37).…”
Section: Observational Studysupporting
confidence: 72%
“…A total of 146 registered trials were identified, including 61 trials in ED and 85 in ICU, which is similar with our previous study for cancer ( 33 ). Over half trials registered after 2017, and it was consistent with the development of industry 4.0, which depended on AI to empower medicine ( 37 ).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The 2012 ImageNet Large Scale Visual Recognition Competition (ILSVRC) competition for object recognition rates, which featured a major breakthrough in large-scale GPU-based deep learning (led by Dr. Jeffrey Hinton's research team on Alex-net) [30], and Google's announcement in the same year of its success in recognizing a cat from YouTube images using deep learning, led to a renewed interest in artificial intelligence research around the world [31]. AI technology is actively used in the medical field as well, and its effectiveness has been demonstrated in various results such as medical image analysis and omics analysis [1,[32][33][34][35][36][37][38][39]. In the field of oncology, the introduction of AI is also being actively studied in tumor screening, including lung and breast cancer [40,41].…”
Section: The Third Ai Boom and Era Of Deep Learningmentioning
confidence: 99%
“…7 Numerous studies are increasingly incorporating ML algorithms across a large variety of domains. [8][9][10] As ML decision-support systems are gradually entering the clinics, it is important to carefully evaluate their utility and performance while realizing their limitations. Importantly, the know-how of these platforms should be expanded from computational biologists to the clinical end users, who should be informed and made aware of the trade-offs between these factors 11 in determining the performance and accuracy of ML pipelines in various clinical contexts.…”
Section: Introductionmentioning
confidence: 99%